Epidemiology, Diagnosis and Control of Infectious Laryngotracheitis in Chickens - Saepulloh, Muharam; ., Darminto (Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Infectious laryngotracheitis (ILT) is an acute, highly contagious respiratory disease of poultry characterized by respiratory disorder such as coughing with blood exudate from the trachea. The disease is caused by Herpesvirus of the family Herpesviridae and subfamily of Alphaherpesvirinae. The virus has been characterized as Gallid herpesvirus-1. ILT is worldwide distribution and has been reported to be present in Indonesia. However, the information on the disease in this country is limited. Spread of the ILT among chickens can be by inhalation or digestion, but ELT virus is not transmitted vertically by eggs . The morbidity rate of the disease is about 90-100% with mortality rate between 10-70%. ILT may reduce body weight gain and reduce egg production, so it causes lost in layers, broilers as well as breeders . Diagnosis of the disease can be based on the isolation and identification of the virus using embryonated chicken eggs. There is no treatment available for ILT, so the control of the disease is mainly by vaccination. To ensure the results of vaccination program, monitoring antibody titres following vaccination is essentially required. The most widely used serological test for antibody monitoring is enzyme-linked immunosorbent assay (ELISA). Keywords : ILT, epidemiology, diagnosis, control, chicken